(untitled) (Western European Journal of Historical Events and Social Science, 2026)
The rapid development of digital technologies, artificial intelligence, and technoscience has significantly transformed contemporary social life, creating new opportunities as well as ethical and spiritual challenges. These developments require a deeper philosophical understanding of the moral boundaries that should guide technological progress. This article aims to examine the spiritual and ethical limits of technoscientific development from a cyberphilosophical perspective, with particular attention to the experience of Uzbekistan and the relevance of international ethical standards. The study employs philosophical analysis, comparative methodology, and interdisciplinary approaches. International frameworks on AI ethics, digital governance, and technological responsibility are analyzed alongside Uzbekistan’s policies and initiatives in digital transformation.